2022
DOI: 10.3390/cancers14153698
|View full text |Cite
|
Sign up to set email alerts
|

Immunology Meets Bioengineering: Improving the Effectiveness of Glioblastoma Immunotherapy

Abstract: Glioblastoma (GBM) therapy has seen little change over the past two decades. Surgical excision followed by radiation and chemotherapy is the current gold standard treatment. Immunotherapy techniques have recently transformed many cancer treatments, and GBM is now at the forefront of immunotherapy research. GBM immunotherapy prospects are reviewed here, with an emphasis on immune checkpoint inhibitors and oncolytic viruses. Various forms of nanomaterials to enhance immunotherapy effectiveness are also discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 236 publications
0
5
0
Order By: Relevance
“…Many chemotherapy approaches are not effective towards reaching the desired outcomes in GBM patient treatment [72,73] . Our team has recently investigated the efficiency and mechanisms of combination Simva and TMZ treatments in GBM and showed that Simva sensitizes GBM cells to TMZ-induced apoptosis [10,20,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many chemotherapy approaches are not effective towards reaching the desired outcomes in GBM patient treatment [72,73] . Our team has recently investigated the efficiency and mechanisms of combination Simva and TMZ treatments in GBM and showed that Simva sensitizes GBM cells to TMZ-induced apoptosis [10,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…TMZ resistance, as a major problem in GBM patient therapeutic strategies, has been investigated for years. Moreover, several compounds and drugs were utilized to enhance the efficacy of TMZ while attenuate the resistance to TMZ to achieve the best approach to treat GBM patients [72][73][74]. Recent investigations have showed that taking statins for a long period of time, could potentially increase the survival of the cancer patients (including GBM) and improve their response to different chemotherapy medications [9,[75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…Several immunotherapy combinations with oncolytic viruses are developing to foster outcomes and minimize adverse effects [ 30 ]. For example, immune checkpoint inhibitors (ICIs) [ 31 ], Chimeric Antigen Receptor T therapy (CAR-T) cells [ 32 ], vaccine therapies [ 33 ], focused ultrasound therapy [ 34 , 35 ], and novel bioengineered nanoparticles [ 36 ] are all in the pipeline for GB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma (GBM) is the most common high-grade primary malignant brain tumor with a poor prognosis [ 1 , 2 ]. It is urgently necessary to develop new therapeutic strategies for GBM with approved treatments due to its poor survival rates [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%